2001
DOI: 10.2460/ajvr.2001.62.119
|View full text |Cite
|
Sign up to set email alerts
|

Determination of optimal immobilizing doses of a medetomidine hydrochloride and ketamine hydrochloride combination in captive reindeer

Abstract: The higher dose requirement of MED-KET administration outdoors, compared with indoors, was explained by factors inherent in the darting technique and the different confinements. The iteration and the prediction methods seem applicable for determination of optimal doses of MED-KET in reindeer. The iteration and the prediction procedures may be used to reduce the number of experimental animals in dose-response studies in other species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 11 publications
1
17
0
1
Order By: Relevance
“…The risk of injury and hyperthermia increased with prolonged induction times. In field situations, long induction times increase flight distance and reduce the chance of recovering an animal (Ryeng, 2001). Jessup et al (1984) reported a mean carfentanil dosage of 30.0 g/kg was effective for remote immobilization of captive mule deer (Odocoileus hemionus), and Caulkett et al (2000) reported an IM injection of 10.0 g/kg carfentanil was effective for immobilizing captive mule deer and mule deerϫwhite-tailed deer hybrids.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of injury and hyperthermia increased with prolonged induction times. In field situations, long induction times increase flight distance and reduce the chance of recovering an animal (Ryeng, 2001). Jessup et al (1984) reported a mean carfentanil dosage of 30.0 g/kg was effective for remote immobilization of captive mule deer (Odocoileus hemionus), and Caulkett et al (2000) reported an IM injection of 10.0 g/kg carfentanil was effective for immobilizing captive mule deer and mule deerϫwhite-tailed deer hybrids.…”
Section: Discussionmentioning
confidence: 99%
“…When the inoculation process was completed, sedation was reversed by intramuscular injection of atipamezole (Antisedan™; Atipamezole 5 mg/ml, Zoetis, UK) at a fixed ratio of 5:1 atipamezole:medetomidine and animals were monitored until they were standing. Despite using recommended drugs and doses being reduced to one-third of those recommended for semi-domesticated reindeer [20], three reindeer (one female, two males) died from acute shock-like complications. Similar complications did not occur during the second round of chemical immobilization using the same drugs and doses.…”
Section: Methodsmentioning
confidence: 99%
“…Animals were divided into two groups according to the inoculation method: one respiratory group (R1, R2, and R3) and one genital group (G1, G2, and G3). Prior to being inoculated with CvHV2, the animals where immobilized with an intramuscular administration of a combination of medetomidine hydrochloride (0.1 mg/kg Domitor; Orion Corporation, Turku, Finland) and ketamine hydrochloride (0.5 mg/kg Ketalar; Pfizer Inc., New York, NY) (29).…”
Section: Cells and Virus Madin-darby Bovine Kidney Cells ([Mdbk] Atcmentioning
confidence: 99%